CFD simulation of turbocharger performance - 195089 Mohd. Nazrol Hisham Musalim (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003